Scavenging dicarbonyls with 5'-O-pentyl-pyridoxamine increases HDL net cholesterol efflux capacity and attenuates atherosclerosis and insulin resistance - Jiansheng Huang; Huan Tao; Patricia G. Yancey; Zoe Leuthner; Linda S. May-Zhang; Ju-Yang Jung; Youmin Zhang; Lei Ding; Venkataraman Amarnath; Dianxin Liu; Sheila Collins; Sean S. Davies; et al. (Elsevier, 2023)
Objective: Oxidative stress contributes to the development of insulin resistance (IR) and atherosclerosis. Peroxidation of lipids produces reactive dicarbonyls such as Isolevuglandins (IsoLG) and malondialdehyde (MDA) that covalently bind plasma/cellular proteins, phospholipids, and DNA leading to altered function and toxicity. We examined whether scavenging reactive dicarbonyls with 5'-O-pentyl-pyridoxamine (PPM) protects against the development of IR and atherosclerosis in Ldlr−/− mice. Methods: Male or female Ldlr−/− mice were fed a western diet (WD) for 16 weeks and treated with PPM versus vehicle alone. Plaque extent, dicarbonyl-lysyl adducts, efferocytosis, apoptosis, macrophage inflammation, and necrotic area were measured. Plasma MDA-LDL adducts and the in vivo and in vitro effects of PPM on the ability of HDL to reduce macrophage cholesterol were measured. Blood Ly6Chi monocytes and ex vivo 5-ethynyl-2'-deoxyuridine (EdU) incorporation into bone marrow CD11b+ monocytes and CD34+ hematopoietic stem and progenitor cells (HSPC) were also examined. IR was examined by measuring fasting glucose/insulin levels and tolerance to insulin/glucose challenge. Results: PPM reduced the proximal aortic atherosclerosis by 48% and by 46% in female and male Ldlr−/− mice, respectively. PPM also decreased IR and hepatic fat and inflammation in male Ldlr−/− mice. Importantly, PPM decreased plasma MDA-LDL adducts and prevented the accumulation of plaque MDA- and IsoLG-lysyl adducts in Ldlr−/− mice. In addition, PPM increased the net cholesterol efflux capacity of HDL from Ldlr−/− mice and prevented both the in vitro impairment of HDL net cholesterol efflux capacity and apoAI crosslinking by MPO generated hypochlorous acid. Moreover, PPM decreased features of plaque instability including decreased proinflammatory M1-like macrophages, IL-1β expression, myeloperoxidase, apoptosis, and necrotic core. In contrast, PPM increased M2-like macrophages, Tregs, fibrous cap thickness, and efferocytosis. Furthermore, PPM reduced inflammatory monocytosis as evidenced by decreased blood Ly6Chi monocytes and proliferation of bone marrow monocytes and HSPC from Ldlr−/− mice. Conclusions: PPM has pleotropic atheroprotective effects in a murine model of familial hypercholesterolemia, supporting the therapeutic potential of reactive dicarbonyl scavenging in the treatment of IR and atherosclerotic cardiovascular disease.